Evidence of Aujeszky’s disease in wild boar in Serbia - Milicevic, V. (BMC Vet Res, 2016)
BACKGROUND: Aujeszky’s disease is a viral disease of suids caused by Suid Herpesvirus 1. The disease has worldwide distribution with significant economic impact. In Serbia, there is neither an Aujeszky’s disease eradication nor national vaccination programme of domestic pigs. Since clinical symptoms of Aujeszky’s disease are not specific, it is important to establish a link between clinical signs and presence of ADV active infection in wild boars. The aim of this study was to investigate the possibility of active infection within wild boar showing signs of ADV and also to examine relationship between isolates from domestic pigs and wild boar. Having in mind that virus has not been previously isolated from wild boars in Serbia, we report the first isolation of Suid Herpesvirus 1 from this species in Serbia. RESULTS: Tissue and serum samples from 40 wild boars from eastern Serbia were examined for evidence of Aujeszky’s disease (AD). Suid Herpesvirus 1 (SHV1), the cause of AD was isolated on PK15 cell line from three tissue samples, inducing cytopathic effect (CPE) with syncytia forming, and viral genome was detected by polymerase chain reaction (PCR) in eight samples. Genetic analysis of us4, us9 and ul49.5 partial sequences showed high homology between ADV isolates from wild boars and between isolates from wild boars and domestic animals. Neutralizing antibodies were not detected by virus neutralisation test (VNT) in sera from four out of eight PCR positive wild boars suggesting recent infection in those animals. CONCLUSIONS: This is the first demonstration of Aujeszky’s disease virus (ADV) in the wild boar population in Serbia although seroconversion has been detected previously.